Distributed converter for high-brightneess bremsstrahlung generation - Biller, E.Z.; Nikiforov, V.I.; Tenishev, A.Eh.; Torgovkin, A.V.; Uvarov, V.L.; Shevchenko, V.A.; Shlyakhov, I.N.; Shramenko, B.I.; Zhiglo, V.F. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
The novel type of the converter to transform a high-density electron beam into bremsstrahlung has been developed and investigated. To increase the thermal stability of the converter by means of a growth of the heat-exchange effectiveness in the area of the bremsstrahlung generation a braking media has been performed as the shot evenly distributed in the cooling water. The results of the computer simulation, thermophysical analysis and experimental study of the converter version on the basis of Pb shot are represented. The possibility of essential increase of the permissible electron beam density as well as reduction of the induced activity and water discharge in comparison with plate- type converter from tantalum is shown. Разработан и исследован принципиально новый тип конвертера плотного пучка электронов в тормозное излучение. Для повышения тепловой стойкости конвертера путем увеличения эффективности теплообмена в области генерации излучения тормозящая среда выполнена в виде дроби, равномерно распределенной в охлаждающей воде. Приведены результаты компьютерного моделирования, теплофизического анализа и экспериментальных исследований варианта конвертера на основе свинцовой дроби. Показана возможность существенного увеличения допустимой плотности пучка электронов, а также снижения наведенной активности и расхода охлаждающей воды по сравнению с пластинчатым конвертером из тантала. Розроблено і досліджено принципово новий тип конвертера щільного пучка електронів у гальмівне випромінення. Для підвищення теплової стійкості конвертера шляхом збільшення ефективності теплообміну в області генерації випромінення гальмуюче середовище виконане у вигляді дробу, рівномірно розподіленого у воді, що охолоджує. Приведені результати комп'ютерного моделювання, теплофізичного аналізу і експериментальних досліджень варіанту конвертера на основі свинцевого дробу. Показана можливість істотного збільшення допустимої щільності пучка електронів, а також зниження наведеної активності і витрати води, що охолоджує, в порівнянні з пластинчастим конвертером з танталу.